2015
DOI: 10.4274/tjod.02439
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnesium sulphate on postoperative analgesia requirements in gynecological surgeries

Abstract: Objective:Recent studies have shown the positive effect of magnesium sulphate (MgSO4) on pain reduction and postoperative analgesic requirements in patients undergoing surgery. We assessed the effect of MgSO4 on intra-operative and postoperative analgesic requirements in patients undergoing lower abdominal gynecological laparotomy.Materials and Methods:This randomized clinical trial was conducted on 30 female patients at Rasool-e-Akram (referral and academic) hospital in Tehran from August 2012 to March 2013. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Various studies of intrathecal magnesium also showed similar findings of extended duration of postoperative analgesia and decreased systemic analgesics requirements thereafter. 15,17,18,20,23,24 Our findings further support the role of magnesium sulfate, an NMDA antagonist, as an effective adjuvant for spinal anaesthesia. NMDA receptor activation leads to synaptic plasticity, wind-up phenomenon and central sensitization, which determines duration and intensity of postoperative pain.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Various studies of intrathecal magnesium also showed similar findings of extended duration of postoperative analgesia and decreased systemic analgesics requirements thereafter. 15,17,18,20,23,24 Our findings further support the role of magnesium sulfate, an NMDA antagonist, as an effective adjuvant for spinal anaesthesia. NMDA receptor activation leads to synaptic plasticity, wind-up phenomenon and central sensitization, which determines duration and intensity of postoperative pain.…”
Section: Discussionsupporting
confidence: 67%
“…5,[14][15][16][17][18] Magnesium sulfate via intrathecal route can be given in the doses like 50,75 and 100 mg. We have used Magnesium sulfate 100 mg intrathecally as it extends the postoperative analgesia, lessens the consumption of analgesics thereafter without increasing side effects. 5,17,[19][20][21] In our study, demographic data were comparable among the two groups. Onset of sensory block and time to achieve peak sensory level were late in Magnesium group in comparison to Tramadol group (p<0.0001).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Total intravenous anesthesia significantly reduced the need for magnesium, propofol, remifentanil and vecuronium in patients undergoing elective spinal surgery [29]. Tramer et al showed that magnesium sulphate infusion in patients undergoing abdominal hysterectomy under general anesthesia reduced PCA morphine consumption and improved sleeping comfort and comfort [35].…”
Section: Discussionmentioning
confidence: 99%
“…Asadollah et al [29] found that, preoperative and continuous infusion of magnesium sulfate was associated with significant decrease in pain score postoperatively with reduced the need to opioid analgesia in patients undergoing lower abdominal laparotomy.…”
Section: Discussionmentioning
confidence: 99%